Regulation of correlative inhibition of axillary bud outgrowth by basal branches varies with growth stage in Trifolium repens - Thomas, Roderick G (Journal of experimental botany, 2015)
© The Author 2015. Published by Oxford University Press on behalf of the Society for Experimental Biology.